A network meta-analysis of anorexia treatments in disease and old age: pharmacogenomics, the gut-brain axis and artificial neural nets. Where are we? - Sofia Korsavva; Filimena Borisova Valkova; Ignacio Calderon Perez (Geriatric Care)
Anorexia affects millions of people worldwide, and treatments vary widely, with no definitive treatment guidelines. A network meta-analysis compared and contrasted existing treatments for chronically ill and elderly patients. EMBASE, MEDLINE, PubMed, Cochrane, and clinicaltrials.gov were searched for articles reporting weight/body mass index changes pre- and post-treatment in the last 65 years. The target population was anorectic adults with chronic long-term illness (cancer, HIV, cystic fibrosis) or the elderly (ages over 65). Outcomes using pooled-weighted-standard-mean effect sizes were analyzed using a random effects model with Bayesian and frequentist methods. Meta-regressions with artificial neural nets were used to validate results and predict response to treatments. A total of 74 studies were included in the network meta-analysis out of the retrieved 340 articles, and 16,390 patients were analyzed in total. The random effects model calculated a pooled-weighted-effect size (p<0.0001) for olanzapine [0.87, confidence interval (CI) 95% (0.66-0.97)], for megestrol acetate high-dose [0.72, CI 95% (0.53-0.91)], for anamorelin [0.56, CI 95% (0.36-0.77)], for megestrol acetate low-dose [0.47, CI 95% (0.25-0.69)], for mirtazapine [0.42, CI 95% (0.13-0.72)], and for nutritional supplementation [0.45, CI 95% (0.29-0.61)]. Cannabinoids, cyproheptadine, other antidepressants, and steroids did not perform well. Between-study heterogeneity was tau-squared (τ2)=0.03. Subgroup analysis indicates that olanzapine is most effective for cancer patients, followed by megestrol acetate in high doses and anamorelin. Results were inconclusive for other patient groups. Olanzapine-induced weight gain is an adverse drug reaction that can be explained by pharmacogenomics affecting gut-microbiota dysbiosis. Compared to megestrol acetate and anamorelin, it has fewer side effects, improves sleep and mood, and has proven anti-nausea/anti-vomiting effects in chemotherapy. Furthermore, it inhibits some types of cancer cells and can be cytotoxic. Drug repositioning of olanzapine and anamorelin for cancer, elderly, HIV, and cystic fibrosis patients as orexigenic agents should be explored further. Appropriate nutritional supplementation should augment anorexia treatments.